KONDISI FISIK OLAHRAGA BULUTANGKIS - Amalia Zahro Siregar; Mawardi Nur; Aulia Rahman; Michael Situmorang (STKIP Subang, 2026)
Badminton is a sport that requires technical, tactical, mental, and physical skills to achieve maximum performance. Physical fitness is a crucial factor because badminton is fast-paced and requires dynamic movements throughout the match. This study aims to determine the importance of physical fitness in badminton, the components of physical fitness required by athletes, and the effect of physical fitness on performance. The research method used was a literature review, collecting data from various books, scientific journals, articles, and reference sources related to physical fitness in badminton. The results indicate that physical fitness significantly influences an athlete's playing ability. Components of physical fitness, such as endurance, strength, speed, agility, flexibility, coordination, and balance, are essential to support athlete performance during competition. Athletes in good physical condition are able to move faster, maintain stamina for longer, produce powerful and accurate shots, and reduce the risk of injury. Furthermore, regular, programmed, and continuous physical fitness training can improve athletes' physical abilities and help them achieve optimal performance. Thus, physical conditioning development should be a major part of a badminton training program.